A LATE PLEISTOCENE RODENT FAUNA (MAMMALIA: RODENTIA) FROM HADŽI PRODANOVA CAVE NEAR IVANJICA (WESTERN SERBIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
Hadži Prodanova Cave in western Serbia is a multilayered site which, in addition to Palaeolithic tools, has yielded a relatively rich fauna of small and large vertebrates. In this paper the rodent fauna from this site is described. In total, 13 species of rodents have been found: Spermophilus cf. citelloides, Sicista subtilis, Mesocricetus newtoni, Arvicola cf. terrestris, Chionomys nivalis, Microtus arvalis/agrestis, Microtus subterraneus, Clethrionomys glareolus, Apodemus sylvaticus, Apodemus cf. uralensis, Spalax sp., Muscardinus avellanarius. This fauna has a mixed character and includes species of both open and forest habitats, the former being more numerous. According to its overall composition, it is tentatively ascribed to a relatively mild and wet period of the Last Glacial, probably MIS 3.